Six years of nitrous oxide emissions from temperate cropping systems under real-farm rotational management - Josette Garnier; Antoine Casquin; Benjamin Mercier; Anun Martinez; Eric Gréhan; Abdel Azougui; Sébastien Bosc; Alexandre Pomet; Gilles Billen; Bruno Mary (Agricultural and Forest Meteorology, 2024)

Is food self-sufficiency possible for Reunion Island? - Gilles Billen; Josette Garnier; Alexandre Pomet; Bernard Bonnet (Regional Environmental Change, 2024)
In the context of political and economic instability, food self-sufficiency of countries and territories is becoming a burning issue. Reunion Island is a densely populated small French territory isolated in the middle of the Indian Ocean. The previously developed GRAFS model, allowing consistent balances to be established using nitrogen (N) as a common metric for all crops and foodstuffs, has been applied to Reunion Island, considering 11 sub-regions to account for landscape variety. Reunion Island dedicates 87% of its crop production in terms of harvested proteins to the exportation of sugar and tropical fruits, while it imports 67% of its food supply, 54% of livestock feed, and 57% of all fertilizing N inputs to agricultural soils. Overall, the supply of 1 tonne of N as food requires the import of 2.7 tonnes of N as food, feed, and fertilizers. The model also demonstrated that the simultaneous operation of three levers of change would make it possible to reach self-sufficiency in terms of food, feed, and fertilizer: (1) the generalization of agro-ecological crop rotations alternating grain and forage legumes, cereal, and other food crops; (2) the reconnection of livestock with crop farming and a better recycling of manure as well as of human excreta; (3) a drastic reduction of animal-based food in the Reunionese diet, down to 20% of animal products in the total per capita protein intake, instead of the 60% current share. The area dedicated to sugarcane cultivation should be reduced to 15–25% of its current value.